Body temperature evaluation in sheep production systems at the Centro de Formación Agroindustrial - Navas, Claudio Mauricio
The objective of this study is to evaluate and compare the body temperature of sheep intwo different habitats: in an environment with a silvopastoral arrangement with scatteredtrees (CS) and in a conventional pasture (SS), established in the Centro de FormaciónAgroindustrial. Two groups of sheep were organized, each one with a specimen of theSanta Inés breed and another of the Katahdin breed. The variables recorded to measureenvironmental conditions were atmospheric temperature (TaºC) and relative humidity (%RH), and rectal body temperature (TrºC) in sheep. The data were descriptively analyzedconsidering the relationship between the two environments, finding that the sheep in SSconditions reached the highest internal body temperature (39.53ºC), directly affected bythe environmental temperature (33.38ºC), but at the same time presented thermal selfregulation,as can be seen when comparing with CS values. The study concludes that the presence of shade within the productive systems in sheep improves the responses of animal comfort in body temperature.